2019
DOI: 10.1101/566018
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple elements of addiction vulnerability are independently heritable in rats

Abstract: Background:Although cocaine is powerfully rewarding, only a fraction of drug-exposed individuals actually transition to become drug-dependent users, possibly due in part to genetic influences, as addictions are among the most heritable of human neuropsychiatric disorders. Consistent with addiction being a complex disorder, prior studies have noted many factors that predict addiction vulnerability, such as drug-induced aversive effects, behavioral responses to novelty, and sensitivity to punishment. Methods:We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Such a large-scale behavioral approach is required to unveil the genetic basis of addiction-like behavior. The evaluation of different addiction-like behaviors is important as multiple elements of addiction vulnerability were found to be independently heritable (Eid et al, 2019 ), and likely controlled by distinct genes that remain to be identified. Previous studies have clearly identified strain differences in the propensity for escalation of drug intake, which speaks to its heritability (Meyer et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such a large-scale behavioral approach is required to unveil the genetic basis of addiction-like behavior. The evaluation of different addiction-like behaviors is important as multiple elements of addiction vulnerability were found to be independently heritable (Eid et al, 2019 ), and likely controlled by distinct genes that remain to be identified. Previous studies have clearly identified strain differences in the propensity for escalation of drug intake, which speaks to its heritability (Meyer et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of different addiction-like behaviors is essential as multiple elements of addiction vulnerability were found to be independently heritable (56), and are likely controlled by distinct genes that remain unidentified. Opioid self-administration and the psychoactive effects of opioids in rodents, like opioid use disorder in humans, have a heritable component.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of different addiction-like behaviors is important as multiple elements of addiction vulnerability were found to be independently heritable (Eid, Pullmann, LI, Thomas, & Jhou, 2019), and are likely controlled by distinct genes that remain to be identified. Inbred strains studies have clearly identified massive strain differences in the propensity for escalation of cocaine use, which speaks to its heritability.…”
Section: Discussionmentioning
confidence: 99%